RUNNING EVENT “TRACKPRESSO: 5K COLOR RUN 2024 DI KOTA SEMARANG, JAWA TENGAH” SEBAGAI PROGRAM MANAGER, PRODUCTION, PIC EVENT, SERTA LIAISON OFFICER DI DALAM RANGKAIAN ACARA - Gracella Rosaline, Maria; Manalu, S. Rouli (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This field project discusses the entire preparation and execution of the Trackpresso: 5K Color Run 2024 event. Anak Panah Kopi, as the client, collaborated with the project team, motivated by the desire to create an event that has been trending in recent months, using the 'riding the wave' strategy as the basis for conducting this project. This report utilizes Integrated Marketing Communication as the conceptual framework, applying eight tools, and event management principles as outlined in Joe Goldblatt's book